Harmine and Harmaline Downregulate TCDD-Induced Cyp1a1 in the Livers and Lungs of C57BL/6 Mice. (20th December 2012) - El Gendy, Mohamed A. M.; El-Kadi, Ayman O. S.
Abstract : We previously demonstrated that Peganum harmala L. extract and its main active constituents, harmine and harmaline inhibit the 2, 3, 7, 8-tetrachlorodibenzo- p -dioxin (TCDD)-mediated induction of the carcinogen-activating enzyme, Cyp1a1, in vitro . However, the effect of both alkaloids on Cyp1a1 in vivo has not been investigated. Therefore, the aim of this study is to examine the effect of harmine and harmaline on TCDD-mediated induction of Cyp1a1 in mice livers and lungs. C57BL/6 male mice were distributed into four groups (n = 6 ). First group received vehicle, while the second group received TCDD (i.p.). The third and fourth groups received either harmine or harmaline (i.p.) × 3 times along with TCDD one time with the mid dose of harmine and harmaline. All mice were sacrificed after 14 h from TCDD injection, and livers and lungs were isolated. The effect of harmine and harmaline on TCDD-mediated induction of Cyp1a1 mRNA, protein, and activity levels was determined using real-time PCR, Western blot analysis, and 7-ethoxyresurofin as a substrate, respectively. Our results showed that harmine and harmaline significantly decreased the TCDD-mediated induction of Cyp1a1 in both the livers and lungs. We concluded that harmine and harmaline are promising candidate to inhibit TCDD-mediated induction of Cyp1a1 in mice hepatic and extrahepatic tissues.